Aberrant expression of bone morphogenetic proteins in the disease progression and metastasis of breast cancer - Liu, Ming; Sui, Laijian; Fang, Ziqian; Jiang, Wen G.; Ye, Lin (Frontiers in Oncology, 2023)
Background: Bone morphogenetic proteins (BMPs) play crucial roles in the tumorigenesis and metastasis of cancers. Controversy remains about the exact implications of BMPs and their antagonists in breast cancer (BC), due to their diverse and complex biological functions and signalling. A comprehensive study of the whole family and their signalling in breast cancer is provoked. Methods: Expression of BMP, BMP receptors and antagonists in breast cancer were analysed by using TCGA-BRCA and E-MTAB-6703 cohorts. ER, PR, HER2 together with markers and regulators of proliferation, invasion, angiogenesis, lymphangiogenesis and bone metastasis were evaluated to dissect the implication of BMPs in breast cancer. Results: The present study showed BMP8B was significantly increased in breast tumours, while BMP6 and ACVRL1 were decreased in breast cancer tissues. The expressions of BMP2, BMP6, TGFBR1 and GREM1 were significantly correlated with BC patients’ poor overall survival. Aberrant expression of BMPs, together with BMP receptors, were explored in different subtypes of breast cancer according to ER, PR and HER2 status. Furthermore, higher levels of BMP2, BMP6 and GDF5 were revealed in triple negative breast cancer (TNBC) whilst BMP4, GDF15, ACVR1B, ACVR2B and BMPR1B were relatively higher in Luminal type BC. ACVR1B and BMPR1B were positively correlated with ERα but were inversely correlated with ERβ. High expression of GDF15, BMP4 and ACVR1B were associated with poorer overall survival in HER2 positive BC. BMPs also play dual roles in tumour growth and metastasis of BC. Conclusion: A shift pattern of BMPs was showed in different subtypes of breast cancer. These BMPs and receptors are actively involved in the disease progression by promoting proliferation, invasion, EMT and distant metastases.